1995
DOI: 10.1177/039139889501801208
|View full text |Cite
|
Sign up to set email alerts
|

Change in Hemorrheological and Biochemical Parameters following Membrane Differential Filtration

Abstract: MDF is a safe and highly effective method for lowering biochemical and improving rheological parameters which led to improvement in visual acuity. We have already replaced plasma exchange with MDF in our clinical practice of hemorrheological therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…The therapeutic effect of Rheopheresis on microcirculatory disturbances can be evaluated by a significant body of clinical data in the treatment of ocular, cerebral, and cardiovascular disorders (5,30). Brunner and coworkers demonstrated in a randomized and controlled clinical study that rheopheresis is safe and effective in improving rheological parameters (plasma viscosity, erythrocyte aggregation) in patients with AMD, led to improvement in visual acuity, and changed the chronic deteriorating natural course of AMD (6,7). These findings recently were confirmed in a second randomized and controlled clinical study in Salt Lake City, UT, U.S.A. (8).…”
Section: Improving Impaired Microcirculation By Rheopheresismentioning
confidence: 93%
“…The therapeutic effect of Rheopheresis on microcirculatory disturbances can be evaluated by a significant body of clinical data in the treatment of ocular, cerebral, and cardiovascular disorders (5,30). Brunner and coworkers demonstrated in a randomized and controlled clinical study that rheopheresis is safe and effective in improving rheological parameters (plasma viscosity, erythrocyte aggregation) in patients with AMD, led to improvement in visual acuity, and changed the chronic deteriorating natural course of AMD (6,7). These findings recently were confirmed in a second randomized and controlled clinical study in Salt Lake City, UT, U.S.A. (8).…”
Section: Improving Impaired Microcirculation By Rheopheresismentioning
confidence: 93%
“…120 % of the patients plasma volume was processed during the first treatment and 80 % during the second treatment. However the study design permitted to process smaller volumes down to 60 % if the plasma protein values at the end of the first treatment were subnormal.Whole blood viscosity was measured with a cone plate system (CS-Rheometer Carri Med Ltd, Dorking, UK) [4]. Plasma viscosity was determined with the capillary tube plasma viscosimeter (Myrenne GmbH, Roetgen, Germany) [12].…”
Section: Methodsmentioning
confidence: 99%
“…Erythrocyte aggregation was measured with the Mini-Aggregometer (Myrenne GmbH, Roetgen, Germany) [13]. The biochemical parameters as total protein, albumin, fibrinogen, IgG, IgM, total cholesterol, triglyerides and LDLcholesterol were determined using standard procedures as described in detail before [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be several interacting mechanisms including: 1) decreased blood viscosity with improved blood rheology [20]; 2) improved coronary microcirculation; 3) lowered oxidized LDL levels [21]; 4) the removal of small, dense LDL and 5) downregulation of leukocyte and endothelial adhesion molecules [18]. Tamai et al [22] measured forearm blood flow while infusing acetylcholine before and after a single LDL apheresis treatment and found that vasodilatation responses were significantly augmented.…”
Section: Mechanismsmentioning
confidence: 99%